TourGuideAI: Revolutionizing Travel with AI and Seamless Integration - Gurbani Gambhir; Kedar Meherkar; Hemang Rathod (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
TourGuideAI is a cutting-edge use of artificial intelligence (AI) in the travel sector that aims to transform how tourists discover new places. Utilizing state-of-the-art artificial intelligence (AI) technologies, the system seamlessly integrates user preferences, real-time data, and interactive elements to deliver tailored travel experiences. By providing personalized itineraries, intelligent navigation, language translation, and suggestions for nearby restaurants, lodging options, and activities, TourGuideAI improves on the conventional trip guide. Each traveler's demands and interests are taken into account by the platform, guaranteeing a dynamic and interesting trip. TourGuideAI's promise to revolutionize tourism provides a window into the future of smart travel, where human experience and technology combine to make travel more accessible, pleasurable, and effective for all.
Keywords: TourGuideAI; artificial intelligence; intelligent navigation; tourism innovation; cloud computing